Nitrogen quadrupole coupling constants for HCN and H2CN +: Explanation of the absence of fine structure in the microwave spectrum of interstellar H2CN+ - Scuseria, G.E. (1985)
Nitrogen 14 quadrupole coupling constants for H2CN+ and HCN are predicted via ab initio self-consistent-field and configuration interaction theory. Effects of electron correlation, basis set completeness, and geometrical structure on the predicted electric field gradients are analyzed. The quadrupole coupling constant obtained for H2CN+ is one order of magnitude less than in HCN, providing an explanation for the experimental fact that the fine structure of the microwave spectrum of H 2CN+ has not been resolved. This research also allows a reliable prediction of the nuclear quadrupole moment of 14N, namely Q(14N)=2.00×10-26 cm2. © 1986 American Institute of Physics.